Health and Well-being: Indispensable in the Lives of all Individuals (International Journal of Preventive Medicine and Health (IJPMH), 2026)
The individuals, belonging to all age groups, genders, occupations, communities, and socio-economic backgrounds, are required to pay attention to health and well-being. This needs to be from physical and psychological perspectives. Throughout individuals' lives, they need to augment their knowledge of factors that promote good health and well-being. All types of factors should be implemented appropriately to generate the desired outcomes. Family members carry out this task during childhood, whereas during adulthood, individuals need to focus on it themselves. As a consequence of promoting good health and well-being from physical and psychological perspectives, individuals will contribute to the upgradation of various skills and abilities. Furthermore, they will perform well in a wide range of job duties and responsibilities in personal life, in educational programs at institutions of all levels, and across a wide range of employment settings. In addition, they will contribute to the upgradation of overall personality traits and standards of living. Hence, individuals need to put in their best efforts to carry out this task in an adequate and well-organised manner. Therefore, it is well-understood that health and well-being are indispensable to the lives of all individuals. The main concepts addressed in this research paper are: understanding the meaning and significance of promoting health and well-being, measures to implement to achieve this, and the advantages of promoting health and wellbeing.